Small business - Tyson, Eric; Schell, Jim (For dummies, 2024)
Easy-to-follow advice on launching, managing, and growing your business, and making it pay off Small Business For Dummies is the essential guide you need to owning and operating a small business. You're ready to add your name to the roster of business owners, and this book is here to give you the advice you'll need at all stages of the game. Start off with insight on preparing to launch a small business, including picking the right business to pursue and getting all the paperwork in order. If you want to purchase an existing business, this book also has you covered. Plus, you'll learn how to wear all the hats a small business owner must wear, including being your own HR manager, accountant, and marketer--and to make it all work. Create a business plan and learn how to fund your business idea Tackle the basics of small business bookkeeping so you can budget for success Explore the idea of purchasing a business, and hire excellent employees Avoid the most common mistakes that first-time business owners make This jargon-free book meets small business owners wherever they are on the road to business success. Small Business For Dummies is great for those just toying with the idea of opening a business, and for those who already call themselves "boss" but need a few extra pointers on making things run smoothly.